2009
DOI: 10.4161/chan.3.2.8609
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+release-activated Ca2+current (ICRAC) mediates store-operated Ca2+entry in rat microglia

Abstract: Channels 129 I CRAC mediates SOCE in microglia [Channels 3:2, 129-139; March/April 2009]; ©2009 Landes BioscienceCa 2+ signaling plays a central role in microglial activation, and several studies have demonstrated a store-operated Ca 2+ entry (SOCE) pathway to supply this ion. Due to the rapid pace of discovery of novel Ca 2+ permeable channels, and limited electrophysiological analyses of Ca 2+ currents in microglia, characterization of the SOCE channels remains incomplete. At present, the prime candidates ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 64 publications
(111 reference statements)
5
74
0
Order By: Relevance
“…Quantitative comparisons of mRNA expression have shown that TRPC1, TRPC3, and TRPC6 are highly expressed in cultured microglia. 17) In line with this finding, double-label immunofluorescence studies show that TRPC3 and TRPC6 are weakly localized in microglia in vivo. 18,19) Recently, Liu et al reported that amyloid β-protein (Aβ) upregulates TRPC6 via nuclear factorkappaB (NF-κB) and promotes the production of cyclooxygenase-2 (COX-2) in BV-2 microglia, which could be involved in microglial activation-induced hippocampus neuronal damage.…”
Section: Physiological and Pathophysiological Roles Of Trpc Channels supporting
confidence: 55%
“…Quantitative comparisons of mRNA expression have shown that TRPC1, TRPC3, and TRPC6 are highly expressed in cultured microglia. 17) In line with this finding, double-label immunofluorescence studies show that TRPC3 and TRPC6 are weakly localized in microglia in vivo. 18,19) Recently, Liu et al reported that amyloid β-protein (Aβ) upregulates TRPC6 via nuclear factorkappaB (NF-κB) and promotes the production of cyclooxygenase-2 (COX-2) in BV-2 microglia, which could be involved in microglial activation-induced hippocampus neuronal damage.…”
Section: Physiological and Pathophysiological Roles Of Trpc Channels supporting
confidence: 55%
“…The qRT-PCR performed on neonatal cultured neonatal rat microglia revealed the following rank of mRNAs expression: (671). The TRPM7 expression was very high and comparable with expression of housekeeping gene HPRT-1 (671).…”
Section: Trp Channelsmentioning
confidence: 96%
“…The Na ϩ currents through store-operated channels demonstrated very slow activation kinetics; the unitary channel conductance was 42.5 pS, and the channels were positively modulated by PKA and negatively by PKC (344). Likely, these currents reflected the activation of TRPM7 channels (671).…”
Section: Ca 2ϩ Release-activated Ca 2ϩ Currentmentioning
confidence: 97%
See 1 more Smart Citation
“…Fura-2 signaling was used to monitor intracellular Ca 2ϩ (Ca 2ϩ i ), according to our standard procedures (Ohana et al, 2009). Astrocytes were loaded for ϳ45 min at room temperature with 3.5 g/ml Fura-2-AM (Invitrogen) diluted in standard bath solution containing the following (in mM): 135 NaCl, 5 KCl, 1 MgCl 2 , 1 CaCl 2 , 5 glucose, 10 HEPES, adjusted to pH 7.4 with NaOH, and to ϳ300 mOsm with sucrose.…”
Section: Methodsmentioning
confidence: 99%